Answer:
the first step to eliminate d is to multiply equation B by 5
second :(m,n) (-6,-11)
value of a can be substituted into equation D to solve the system of equations is 7b-1
Step-by-step explanation:
first equation:
4c=d-8 or 4c-d=-8
c=5d+8 or c-5d=8
so the first step to eliminate d is to multiply equation B by 5
second equation :
n=3m+7 or n-3m=7
n-2m=1
n-3m=7
solve :
1-eliminate n by subtracting two equation : : n-2m-(n-3m)=1-7
-2m+3m=-6
m=-6
substitute m: n-3(-6)=7 , then n+18=7
n=7-18=-11
third :
a=3b+6 or a-3b=6
a=7b-1
find a
a-3b=6
value of a can be substituted into equation D to solve the system of equations is 7b-1